Tools for the Assessment of Pediatric Restless Legs Syndrome - Stubbs, Pamela Hamilton; Walters, Arthur S. (Frontiers in Psychiatry, 2020)
Background: There are a few of the questionnaires for the diagnosis, severity and quality of life of adult Restless Legs Syndrome (RLS) that are utilized but not yet validated in children. Even fewer of these types of instruments have been developed specifically for Pediatric RLS. Methods: This article is a review of instruments used in adult RLS, their applicability to children and of instruments specifically developed for childhood RLS. Results: A single question for the diagnosis of RLS has been validated for adults and utilized in one epidemiology study of adolescents with RLS. The Pediatric Emory RLS questionnaire has been developed as a diagnostic instrument for childhood RLS, utilized in two studies of RLS in children, but not yet validated. The IRLS (International Restless Legs Scale), the CGI (Clinical Global Impression), and the RLS-6, which have been utilized for determining adult RLS severity, were administered without difficulty in one therapeutic study of adolescent RLS. In addition, the IRLS has also been utilized in another 5 studies of childhood and adolescent RLS. The pediatric Restless Legs Syndrome Severity Scale (P-RLS-SS) has been developed for use in children but not yet validated. A modification of the P-RLS-SS based upon rating the severity of the 4 diagnostic criteria for RLS has been developed for children but not yet validated. There are no Quality of Life Studies developed for Pediatric RLS. However, 3 separate studies utilized the general Peds Quality of Life Inventory (PedsQL) in RLS children and adolescents and one of these studies also employed the general Sleep Behavior Questionnaire (SBQ) and yet another of these studies also employed the Pediatric Symptom checklist (PSC). Discussion: There is a need for the development and validation of instruments specific to Pediatric RLS. Meanwhile, we recommend the use of the Pediatric RLS instruments that have been developed and we recommend use of the adult scales in adolescent RLS where language barriers are not a problem. If adult scales are used in younger children, we recommend that they be administered in conjunction with an ongoing discussion between the parent and the child during the scale administration.